Abordagem clínica de cordeiros prematuros: avaliação de protocolos terapêuticos emergenciais para estimulação da atividade respiratória - Bovino, Fernanda [UNESP] (2015)
The objective was to evaluate the efficacy of different therapeutic protocols in clinical and laboratory approach of premature lambs to stimulate respiratory activity. Four groups were formed: group I (n=6) included lambs without treatment; group II (n=9) included lambs born to mothers that were treated with dexamethasone antepartum; group III (n=6) included lambs treated with surfactant; and group IV (n=6) included lambs treated with surfactant and born to mothers that were treated with dexamethasone antepartum. Physical, thermal, radiographic and spirometric evaluation were performed after birth (T0), 15 minutes later (T15), one hour (T1), six hours (T6), 12 hours (T12), 24 hours (T24) and 48 hours after birth (T48). Blood samples were taken at the same time to perform blood gas analysis, liver and renal profile, blood glucose, blood lactate and serum concentration of insulin and cortisol. After birth to T48, all the lambs showed low pH values, which were associated with high pCO2 values and HCO3 . There was a decrease in RBC, HCT, MCV and HGB in the first 48 hours. Creatinine serum concentrations was decreased to the T48 . There was an increase of lactate to the T1, with a reduction to the T48. Premature lambs showed low vitality and impaired pulmonary function. The use of surfactant should be performed in combination with maternal antepartum dexamethasone administration. Changes in blood count and biochemical profile are physiological variations. Thermal imaging can be used for analysis and monitoring of temperatures.